Double network shape memory hydrogels activated by near-infrared with high mechanical toughness, nontoxicity, and 3D printability - Dai, W.; Guo, H.; Gao, B.; Ruan, M.; Xu, L.; Wu, Jian-Ping; Brett Kirk, T.; Xu, J.; Ma, D.; Xue, W. (Elsevier BV, 2019)
In this work, near-infrared (NIR)-responsive double network shape memory hydrogels were formed by chemically cross-linking Pluronic F127 diacrylate macromer (F127DA) and physical blending of poly(lactide-co-glycolide) (PLGA) with graphene oxide (GO, an energy convertor to convert NIR irradiation to thermal energy). The hydrogels were manufactured with 3D-printing technology using ultraviolet light polymerization. The morphologies and crystalline structure of the hydrogels were determined by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The NIR and thermal activated shape memory properties, mechanical toughness, and cytotoxicity were investigated. The shape memory properties were improved by incorporating GO into the hydrogels and the mechanical properties were enhanced by the addition of PLGA, which served as a second network. The cytotoxicity was assessed by the CCK-8 assay, which revealed no cytotoxicity. The nontoxicity, high mechanical toughness (3.45 MPa in the swollen state), and biosafety at the shape recovery temperature (36 ± 1 °C), which was achieved by NIR stimuli, indicates that shape memory hydrogels can be used in biomedical materials safely. The practical potential of the F127DA/PLGA/GO hydrogels was further revealed by their 3D-printing performance, their shape fixity ratio greater than 85%, and their shape recovery time under 300 s. Our results propose that F127DA/PLGA/GO hydrogels will be a promising material in biomedical applications as a drug carrier and an antibacterial scaffold.